Numerical Analysis of Gravitational Vortex Chamber - Zehad, Shahadat Hossain; Faiyaz, Sadman Al; Islam, Md. Redwan; Ahmed, Dr. -Ing. Irfan (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
A rotating mass of fluid is known as vortex and the motion of the rotating mass of fluid is known as vortex motion. Vorticity is the circulation per unit area. In this research simulation of a vortex chamber is to be carried out in ANSYS CFD taking water as fluid domain for generating a water vortex that is capable enough to move a turbine for electricity generation. The CAD modelling of the setup was set down and simulation was done in fine mesh by taking suitable wall function in the model of a cylindrical chamber along with a rectangular channel with a contraction portion at the end of it where good amount of vortex generation was acquired by observing velocity and pressure by setting different parameters. The results shows the pressure and velocity contours with 3D velocity streamline flow and the curve of the velocity and pressure curve shows the decrease of pressure and increase of velocity from inlet to outlet that leads to a decent vortex generation.